The influence of El Nino on water shortage area in Sa Kaeo province, Thailand by using GIS - Noichaisin, L; Buranapratheprat, A.; Manthachitra, V.; Intarawichian, N. (International Journal of Agricultural Technology, 2019)
The influence of El Nino on the area of land impacted by water shortage in Sa Kaeo Province, Thailand was recorded by using Geographic Information System (GIS). As results, the normal conditions revealed that water shortage based on many criteria, average annual rainfall from 30 years, volume of groundwater, distance of water and irrigation sources, soil drainage, slope, and land use. In the year with El Nino phenomenon, the studied criteria were resulted as the same as normal years, except rainfall data from 2015, because it is strated to faced this phenomenon in Thailand. The results indicated that El Nino influenced the degree of water shortage in area of Sa Kaeo Province. The total area with moderate and low water shortage decreased, while the area with high and very high water shortage increased as compared to normal years. The high water shortage area increased from 3,406.19 km2 to 4,489.80 km2 (15.06%). The very high water shortage area increased from 203.17 km2 to 762.22 km2 (7.77%). Preparation of mitigate, the effects of drough from El Nino can should be separated into three phases; before, during, and after. Before an El Nino year, relevant government agencies should determine agricultural production targets in drought condition and plan irrigation management. During the El Nino year, activities should include the monitoring of weather condition and water suppy, Royal rain-making operations, water allocation planning, support for agricultural production, and damage survey for assistance and subsidy. After the phenomenon, mitigation and careers revitalization should be appropriately offered to people in area affected by water shortage.